Effects of commercial organic fertilizer and poultry manure on soil properties, yield and proximate composition of radish (Raphanus sativus L.) (Agriculture, Food, and Natural Resources Journal, 2025)
Organic fertilizer is known for its ability to improve soil fertility and enhance the availability of nutrients to the plant. To examine the impacts of commercial organic fertilizer (Agrodyke) and poultry manure on soil parameters, yield, and the proximate composition of radish (Raphanus sativus), as well as residual effects, a pot experiment was carried out at Bukola Farm in Oke Oyi, Kwara State, Nigeria. Ten treatments were used in the experiment: Control (T0), Agrodyke 10g (T1), Agrodyke 20g (T2), and Agrodyke 30g (T3) in 1.5, 3, and 4.5 litres of water respectively, Poultry manure – 90 kgN/ha (T4), poultry manure – 100 kgN/ha (T5), poultry manure – 110 kgN/ha (T6), poultry manure – 120 kgN/ha (T7), poultry manure – 130 kgN/ha (T8), and NPK (T9). Three replicates were used in the completely randomized design (CRD) of the experiment. Data collected were subjected to analysis of variance (ANOVA), and differences in the treatment means were separated using Duncan's Multiple Range Test (DMRT) at 5 % level of significance. Application of poultry manure at 130 kg N/ha (T8) resulted in maximum values of growth and yield attributes, viz., number of leaves (15.1), stem girth (32.39 mm), root yield (126.8 g), and leaves weight (47.4 g). The residual nutrients and proximate composition, viz., ash, moisture content, crude fiber, and crude fat, in roots were also reported maximum by the application of poultry manure at 130 kg N/ha. Therefore, it can be concluded that using poultry manure increased radish quality and had better residual nutrients than NPK and Agrodyke organic fertilizer.
Keywords: Fertilizer; Poultry manure; Raphanus sativus; yield